2020
DOI: 10.1097/dad.0000000000001612
|View full text |Cite
|
Sign up to set email alerts
|

Tumoral Melanosis in the Setting of Targeted Immunotherapy for Metastatic Melanoma—A Single Institutional Experience and Literature Review

Abstract: Background: Tumoral melanosis clinically resembles metastatic melanoma, occurs in the context of regressed disease, and requires evaluation to rule out underlying melanoma and metastatic disease. Histopathology demonstrates a nodular infiltrate of melanophages in the dermis, subcutaneous tissue, deep soft tissue, or lymph nodes in the absence of viable melanocytes. Recent limited reports of tumoral melanosis in the context of immunotherapy with ipilimumab (monoclonal antibody targeting CTLA-4) as well as nivol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Jurgens et al reported the largest series to date with ten cases. TM mainly appeared in the proximity of the primary tumor within two to twenty months after immunotherapy start [12]. Most cases described in this report showed a favorable clinical response, with nine out of ten patients being alive after the follow-up period [12].…”
Section: Clinical Lettermentioning
confidence: 65%
See 1 more Smart Citation
“…Jurgens et al reported the largest series to date with ten cases. TM mainly appeared in the proximity of the primary tumor within two to twenty months after immunotherapy start [12]. Most cases described in this report showed a favorable clinical response, with nine out of ten patients being alive after the follow-up period [12].…”
Section: Clinical Lettermentioning
confidence: 65%
“…Exceptionally, it has also been reported in regressed pigmented epithelial lesions [8]. As in our case, its metastatic appearance makes a skin biopsy necessary, with immunohistochemistry demonstrating positivity for CD68 and absence of neoplastic cells with SOX-10, HMB-45 and Melan-A [5][6][7][8][9][10][11][12]. The prognosis is still unclear due to the limited number of reported cases with long-term follow-up so far [5][6][7][8][9][10][11][12].…”
Section: Clinical Lettermentioning
confidence: 81%
“…Tumoral melanosis usually presents as black or blue macules, papules or nodules clinically resembling a melanoma or cutaneous metastases. Because of this similarity, skin biopsy is essential for the diagnosis [ 35 ]. Histopathology of tumor melanosis demonstrates a large collection of melanophages and melanin pigment in subcutaneous tissue or dermis associated with the lack of melanocytes.…”
Section: Melanosismentioning
confidence: 99%
“…In the majority of cases reported so far, tumoral melanosis was found in proximity to the primary melanoma or in transit metastases [ 36 , 38 ], although three patients presented with tumoral melanosis at a distant site from the primary melanoma [ 35 ].…”
Section: Melanosismentioning
confidence: 99%
See 1 more Smart Citation